pedestrian railway crossing, level crossing, traffic safety, pedestrian, accident rate coefficient - Yaroslav Bolshelarskyi; Mykola Berezovyi; Piotr Gołębiowski; Oleksandra Orlovska; Yuriy Tereshchak (Transport Technologies)
Applying the Ishikawa and the Bow-Tie techniques to identify root causes in a real-life passenger injury case while boarding a suburban train is examined, the effectiveness of existing control measures (barriers) is analyzed, and new ones are proposed in the article. The issue of enhancing passenger safety in suburban railway transport remains relevant despite the general downward trend in the number of railway incidents in Ukraine. Following signing the Association Agreement with the European Union, Ukraine undertook obligations to implement European standards and practices, including those related to risk assessment and the investigation of railway incidents as part of the overall risk evaluation process. However, the techniques for identifying root causes, as defined in ISO 31010:2019, have not yet been implemented in forensic expert practice or official and technical investigations. A real railway incident that was previously subject to forensic examination – a case of passenger injury during boarding an electric multiple unit train is analyzed in this study. Root causes and the central event – trapping the passenger’s limb by the train doors – were identified using techniques provided by ISO 31010:2019. The paper outlines the application areas for these techniques and presents a comparative analysis. Potential consequences of the central event were examined, along with the existing barriers between root causes and the central event, and between the central event and its consequences. New barriers aimed at mitigating the effects of the central event are proposed. The scientific novelty of the research lies in the application of European approaches to root cause identification of railway incidents, which had not previously been applied in domestic expert or investigative practice. The practical value of this study is in demonstrating the introduction of new root cause analysis techniques into forensic practice and certified forensic methodologies. Further research should focus on applying ISO 31010:2019-compliant root cause analysis techniques to other types of railway incidents, such as derailments, rolling stock collisions, and strikes involving vehicles or pedestrians, as well as on the use of additional techniques outlined in ISO 31010:2019 to enhance railway safety.